The Influence of Price Perceptions, Product Quality and Service Quality on Customer Satisfaction - Instianti Elyana; Rini Martiwi; Fera Nelfianti; Eulin Karlina; Nyoman Suardhita (Quantitative Economics and Management Studies, 2023)
This study aims to determine the effect of perceived price, product quality and service quality on customer satisfaction at PT Dafnet Media Gemilang in Bojonggede District, Bogor Regency. This study used a quantitative descriptive method by distributing questionnaires via Google Form to PT Dafnet Media Gemilang subscribers in Bojonggede District, Bogor Regency. The population in this study was 1200 people in Bojonggede District who were PT Dafnet Media Gemilang customers. Meanwhile, the number of samples was 120 people with the sampling technique used was the Slovin technique. In analyzing the data, this study used SPSS 26 to calculate the results of the Multiple Linear Regression variable test, t test, F test, and determination analysis. The results of this study indicate that based on the t test, price perception, product quality and service quality have a positive and significant effect on customer satisfaction on PT Dafnet Media Gemilang in Bojonggede District, Bogor Regency. Based on the results of the F Test, price perception, product quality and service quality together have a significant effect on customer satisfaction at PT Dafnet Media Gemilang in Bojonggede District, Bogor Regency. Based on the results of multiple regression analysis, the effect of perceived price, product quality and service quality on customer satisfaction at PT Dafnet Media Gemilang in Bojonggede District, Bogor Regency is 76.5% while the remaining 23.5% is influenced by other variables not examined in this study.